A Development of Electrical Vehicle Charging System Using Wireless Power Transfer - Amaluddin, Zainuddin; Syafeeza, Ahmad Radzi; Mazree, Ibrahim; Norihan, Abdul Hamid (Asian Research Publishing Network (ARPN), 2016)
Wireless power transfer is a method of transferring electrical energy from power source to electrical load without any wire connections. It is used to supply the power on electrical devices without any physical connection except air as the medium transfer. In this paper, the design of wireless power transfer charging system for electric vehicles using inductive resonance coupling method will be presented. The purpose of this project is to develop a prototype of electrical vehicle (EV) charging system by wireless power transfer using inductive resonance coupling method. Besides, the performance of wireless power transfer prototype using this method will also investigate. This paper are carried out with the theoretical studies of inductive resonance coupling method, design proposed, circuit simulation and prototype development. The prototype were consists of a few components which are power supply, transmitter/receiver coil with circuits and charging circuit for EV battery. Observation from the prototype experimental show that, power supply can be transfer wirelessly through transmitter and receiver circuit using inductive resonance coupling principles. Other than that, the performance of electrical vehicle charging system are depends on distance of transmitter and receiver coils, period of charging and amount of power sources.